Energy storage for power systems - Ter-Gazarian, A. (Institution of Engineering and Technology, 2011)
Annotation covers both existing energy storage techniques and power system considerations for energy storage and storage applications n ideal for university teachers and students who specialise in power systems development Contents: Trends in power system development. Energy storage as a structural unit of a power system. Storage applications. Thermal energy. Flywheels. Pumped hydro. Compressed air. Hydrogen and other synthetic fuels. Electrochemical energy. Capacitor banks. Superconducting magnetic energy. Considerations on the choice of a storage system. Integration. Effect on transient regimes. Optimising regimes for storage.
Keywords: Energy storage.; Power-plants.; elektronické knihy; electronic books